2017
DOI: 10.3889/oamjms.2017.048
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FGFR3 Protein and Gene Amplification in Urinary Bladder Lesions in Relation to Schistosomiasis

Abstract: BACKGROUND:Bladder cancer represents the fifth most common malignancy worldwide and a major cause of cancer-related morbidity and death. Incidence and mortality rates have remained relatively constant over the past four decades. Urothelial bladder cancers have identified multiple risk factors.AIM:We aimed at evaluating the expression of the FGFR3 protein and gene amplification in the urothelial cells of neoplastic and non-neoplastic urothelial lesions of the urinary bladder, and correlation with tumour grade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…As for immunostaining for FGFR-3 expression, the current study showed that only 24 cases showed negative staining and the remaining 66 cases (73.3% of total cases) showed positive cytoplasmic and/or membranous. Hammam et al [11] also found that 72% of malignant cases in their study were also positive for FGFR3 immunostaining, which is compatible with another study [10] that stated that expression of FGFR3 was found in approximately 70% of both low and high-grade tumors, as well as equally distributed between invasive and non-invasive urothelial carcinoma. Evaluation of the results of immunostaining for COX-2 showed that only 15 cases were negative with the remaining 75 cases (83.3% of total cases) showed positive cytoplasmic and/or membranous reactivity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As for immunostaining for FGFR-3 expression, the current study showed that only 24 cases showed negative staining and the remaining 66 cases (73.3% of total cases) showed positive cytoplasmic and/or membranous. Hammam et al [11] also found that 72% of malignant cases in their study were also positive for FGFR3 immunostaining, which is compatible with another study [10] that stated that expression of FGFR3 was found in approximately 70% of both low and high-grade tumors, as well as equally distributed between invasive and non-invasive urothelial carcinoma. Evaluation of the results of immunostaining for COX-2 showed that only 15 cases were negative with the remaining 75 cases (83.3% of total cases) showed positive cytoplasmic and/or membranous reactivity.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, this study displayed no linear correlation between COX-2 expression and tumor size. Thus, these interesting results similarly supported by Hammam et al [11], who argued that COX-2 may have more of a tumorigenic role rather than a prognostic impact.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…FGFR3 and FGFR4 amplifications are less common and less well studied than FGFR1 and FGFR2 amplifications. FGFR3 amplification is the most common FGFR amplification event in urothelial/bladder cancer [ 189 , 206 , 207 , 208 ].…”
Section: Fgfr Genomic Aberrations In Cancermentioning
confidence: 99%
“…However, in North Africa, especially Egypt, major strides have been made over the years to establish the molecular basis of schistosomiasis and bladder cancer. A case-control study by Hammam et al [23] in Egypt assessing the expression of the fibroblast growth factor receptor (FGFR3) protein, gene amplification in bladder cancer, and associated schistosomiasis revealed that FGFR3 was considerably associated with bladder cancer tumor-grade and stage. Another data from Egypt by Elmansy et al [24] assessing association of Fas and FasL in human bladder cancer with schistosomiasis found that the association of schistosomiasis with bladder cancer raised the incidence of Fas positive immunoreactivity to 100%.…”
Section: Genetic and Immunohistochemical Profile Of Schistosoma Bladdmentioning
confidence: 99%